Medical Parasitology Laboratory: A Self-Directed Learning Module - Melphine Harriott (Association of American Medical Colleges, 2016)
Abstract Introduction This self-directed study on medically relevant parasites was developed as part of an infectious disease course during the M2 year for medical students. It was designed to reinforce the concepts covered during the lecture sessions and review the microscopic morphologies of select parasites. Although medical students and physicians are not necessarily expected to be experts on the microscopic morphologies of parasites, microscopic images of parasites may be included on boards or in-service exams. Methods This resource includes a 46-minute video that reviews the major microscopic features of select medically relevant parasites as well as a postmodule quiz. The video covers select nematodes, cestodes, trematodes, and protozoa. This resource was utilized as a self-directed laboratory during an infectious diseases course for second-year medical students. The video reviews the parasitic pathogens covered during the didactic sessions and does not cover any new information. Results The video was posted on the learning management system, and students were expected, but not required, to view the video. There was no specific assessment for this module, however students were notified that images from the video might be included on exam questions or on laboratory image quizzes. Unfortunately, we were unable to obtain accurate statistics regarding the students' access of the video. Discussion In the past, this session was presented as a wet lab. We noted that student performance on laboratory quizzes was not significantly affected by the self-directed laboratory when compared to the previous wet laboratory. In the future we plan on requiring students to view the video by a certain date, then utilizing the postmodule quiz as an assessment.